Perlindungan Tenaga Kerja Indonesia (TKI) di Luar Negeri melalui Pemberian Jaminan Sosial Ketenagakerjaan - Tioma R. Hariandja (Fakultas Hukum Universitas Islam Jember, 2018)
Social Security for Indonesian Workers is a social security provided to one group of citizens who need to receive social security in this case Indonesian Migrant Workers (TKI) abroad. One of the causes of TKI abroad is because the government has not provided social security for the community, besides their motivation to go abroad, including education, health care costs, as venture capital and as capital preparation in old age. This proves that now people have begun to think about having social security. The government has begun to provide some social security for the poor, through Jamkesmas and free education, but not yet maximally. While guarantees for migrant workers abroad, the government only requires participation in insurance, where insurance guarantees are paid for by the TKI on departure.